EXPERIENCE OF USING DR. ARABIN'S GYNECOLOGICAL PESSARY IN CLINICAL PRACTICE - Светлана Ивановна Елгина; Лариса Юрьевна Меховская; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес (The Publishing House Medicine and Enlightenment, 2020)
Aim - to determine the effectiveness of Dr. Arabin gynecological pessaries in the treatment of pelvic floor muscle failure in elderly women. Materials and methods. A solid method was used to select 41 women aged 60 to 80 years with pelvic floor muscle insufficiency and obvious or hidden urinary incontinence. All patients were divided into 2 groups: A (n = 27), patients with pelvic floor muscle insufficiency of 2-3 degrees who did not want to undergo surgical treatment; B (n = 14), patients with pelvic floor muscle insufficiency of 2-3 degrees who were scheduled for surgical treatment. All women used Dr. Arabin gynecological pessary (cubic pessary with wplk button perforated). Treatment outcomes were studied 6 months after the start of using the Dr. Arabin gynecological pessary. The primary outcome of treatment was the frequency of overt and covert urinary incontinence (cough test and Valsalva test); the secondary outcome of treatment was the frequency of pelvic pain and dyspareunia, and the degree of prolapse according to the Baden - Walker classification. Results. After 6 months, patients using the gynecological pessary Dr. Arabin less experienced symptoms of overt and hidden, determined by a cough test and a Valsalva test, urinary incontinence; less complained of pelvic pain and dyspareunia. Ten patients of group B after 6 months of using the gynecological pessary Dr. Arabin refused the previously offered surgical treatment. The study confirms the fact of independent conservative treatment with Dr. Arabin gynecological pessary in women with pelvic floor muscle insufficiency. Conclusion. The use of gynecological pessaries Dr. Arabin is an effective method of treating pelvic floor muscle insufficiency of 2-3 degrees in elderly women who do not want to undergo surgical treatment.